2020
DOI: 10.1007/s11739-020-02542-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood ozonization in patients with mild to moderate COVID-19 pneumonia: a single centre experience

Abstract: The emerging outbreak of the coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to spread worldwide. We prescribed some promising medication to our patients with mild to moderate pneumonia due to SARS-CoV-2, however such drugs as chloroquine, hydrossichloroquine, azithromycin, antivirals (lopinavir/ritonavir, darunavir/cobicistat) and immunomodulating agents (steroids, tocilizumab) were not confirmed as effective against SARS-CoV2. We, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
51
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 19 publications
6
51
0
6
Order By: Relevance
“…It is expected that older patients show worst clinical outcomes, but Ozone was effective even in older COVID-19 patients 11 . As far as we know, our study has treated the oldest patients, if compared with other ozone studies [21][22][23][24] . 21 .…”
Section: Discussionmentioning
confidence: 98%
“…It is expected that older patients show worst clinical outcomes, but Ozone was effective even in older COVID-19 patients 11 . As far as we know, our study has treated the oldest patients, if compared with other ozone studies [21][22][23][24] . 21 .…”
Section: Discussionmentioning
confidence: 98%
“…In a very recent paper by Tascini et al, the authors reported that, using oxygen-ozone (O 2 –O 3 ) via auto-hemotherapy (O 3 -AHT) in patients with mild to moderate pneumonia, statistically significant improvements occurred in 53% of O 3 -AHT patients respect to controls treated with the solely best available therapy (BAT) [ 1 ]. The authors, moreover, reported that O 3 -AHT treated patients showed a reduced extent in the clinical stability, yet this statement appears garbling and we would like to be elucidated about its meaning [ 1 ]. The overall impression we hold from reading this article is that Tascini et al, performed quite a pre-test, for assessing ozone effectiveness, rather than a complete therapic protocol on patients, following elsewhere reported methods [ 2 ].…”
mentioning
confidence: 99%
“…Flaws are therefore present due both to poor statistics and lacking standardized protocols of therapy. Despite the declared difference in age and disease severity between patients selected to undergo O 3 -AHT supporting BAT and patients with only BAT, the Wilcoxon signed rank test for this matching gives p = 0.92956 for the whole data and p = 0.94761 for data under the heading BGA-Admission (ref Table 1 in ref [ 1 ], suggesting that differences in the separate cohorts of patients were due to chance for a probability higher than 92%, i.e. that the cohorts actually belong to the same population of recruited subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Hernández A et al, in a prospective case–control study, confirm that ozonated autohemotherapy was associated with a significantly shorter time to clinical improvement [ 4 ]. In this study the total dose of gas mixture oxygen-ozone administered was similar to the one used in own study [ 2 ] even if spread over five consecutive days [ 4 ].…”
mentioning
confidence: 99%